PENGARUH KUALITAS PRODUK TERHADAPLOYALITAS PELANGGAN SPRITE : Survei pada para pengunjung Unit PelaksanaTeknis Olahraga ITB/SABUGA - Luqi Luqmanul H, - (2009)
This study aims to find out the Product Quality Impact On Customer Loyalty At Sprite products Technical Implementation Unit Online Sports ITB / Bandung Sabuga. Research methods used in this research is analytical descriptive method and techniques used are incidental sampling technique. Samples in this study were 100 guests UPT Sports ITB/Sabuga. Data analysis techniques in this study using multiple linearregression. The results showed that the simultaneous influence on product quality is consumer loyalty while the remaining 94.4% and 5.6% influenced by other factors. There partially positive influence on the dimensions of performance (13.3%), conformance (15.1%), durability (36.3%), the serviceability (27.1%), aesthetic (11%), and perceived quality (11.3%). It necessary to increase product quality Sprite, so marketers are more sensitive to customers' wants and needs, so customers always consume Sprite, and can enhance customer loyalty to the company.